1 Samuel 25:23–28 and Conflict Resolution in Nigeria: A Literary Reading - Agbasianya, Maria Nneka; Uroko, Favour Chukwuemeka (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This study aims to explore the application of the biblical passage 1 Samuel 25:23–28 in addressing and resolving conflicts in Nigeria. The study identifies several key conflict resolution strategies from Abigail’s actions, including humility, strategic communication, proactive peacemaking, and the appeal to higher principles. These strategies are found to be relevant and potentially effective in addressing conflicts in Nigeria, particularly in contexts marked by ethnic, religious, and political tensions. Nigeria, Africa's most populous nation, is a country rich in cultural diversity, natural resources, and economic potential. However, it has been beset by numerous conflicts over the years, ranging from ethnic and religious violence to political instability and resource-based disputes. The aphorism in I Samuel 25:23–28 is important in understanding the underlying causes and dynamics of these conflicts, and it is essential for developing effective resolution strategies. Data is gathered from biblical commentaries, theological texts, and scholarly articles. Emerged themes are: i) respect and humility; ii) taking responsibility and mediation; iii) acknowledging wrongdoing and deflecting blame; iv) appealing to higher principles; v) offering reparation and tangible solutions; and vi) seeking forgiveness and affirming positive outcomes. These strategies are found to be relevant and potentially effective in addressing conflicts in Nigeria, particularly in contexts marked by ethnic, religious, and political tensions. Abigail's approach, characterised by humility, tact, and moral persuasion, can serve as a model for contemporary peacemakers.